Independensi dan Keunikan Ilmu Hukum dalam Tinjauan Ontologi, Epistemologi dan Aksiologi - Sifaul Amin (Jurnal Multidisiplin Madani, 2022)
The discourse on the status of legal science included in the category of science or not science has always been a matter of debate. The difference between the empirical and normative schools of thought gives rise to differences in perception, making it a never-ending problem, especially in Sui Generis jurisprudence. Studying through the philosophy of science becomes an effective way to solve these problems based on the ontological, epistemological, and axiological aspects. The development of legal science through the realm of research is a challenge that must be done in order to achieve solutions to various problems in society. This research is a qualitative research using a philosophy of science approach so that a conclusion is obtained that philosophically, legal science is included in the category of science. Legal science is also a substantial study of the rule of law that comes from one's own mind and is useful for the process of developing and applying legal science.